Model kinetika perubahan kualitas mangga arumanis (Mangifera indica L.) selama rantai pasok - Listiana Ningrum; Endang Warsiki; Y Aris Purwanto; Siti Mariana Widayanti (AGROINTEK, 2023)
During the supply chain activities, Arumanis mango as climateric fruit experiences quality changes due to the respiration process after being harvested. To find out the quality changes of Arumanis during their supply chain activities, it is necessary to simulate supply chain storage during land, sea, and air shipments in the laboratory. This study aims to predict changes in the quality of Arumanis during supply chain activities to retail storage. The supply chain simulation was carried out in 3 scenarios based on the delivery destination and transportation, including refrigerator trucks, ships, and planes. The temperature of the rooms used in the simulation was 10-12°C as the storage temperature for refrigerator trucks, aircraft cargo, and distribution center storage. The temperature at 20-22°C was used as retail storage temperature. Meanwhile, temperature at 24-28°C was used as the storage temperature for ships. The shipping duration used is 2 and 4 days. The parameters observed in this study were the concentration of carbon dioxide and total soluble solids. The results showed that the reaction kinetics model of quality changes Arumanis mango in all suitable supply chain scenarios was ordo 0 reaction seen from the higher correlation coefficient (R2). The shelf life of arumanis mangoes in all supply chain scenarios reached 8 days of storage. The development of this kinetics model can help to predict the quality changes of Arumanis mangoes during supply chain storage from distribution center to retail.